Letter from Emma Morgan to Julia Morgan, May 14, 1899 - Emma Morgan::::::author::: (1899)
The ink on this letter has bled due to water damaged, contents are readable with difficulty. Only the first two pages of this letter are digitized, there are more pages available in the physical folder.